Sustainability reporting in hospitality sector - Carvalho, L.; Paiva, I. (Strategic business models to support demand, supply, and destination management in the tourism and hospitality industry, 2020)
Students seldom contemplate the importance of sustainability in family businesses. Indeed, the economic dimension of sustainability using performance statements remains a neglected field of study. The case of a Spain family firm in the tourism sector, Meliá Hotels International, is used to introduce students to sustainability analyses through the study of the company’s sustainability information. This provides instructors with an opportunity to discuss the actual financial state of the company and how to improve some indicators, as well as to present an overview of the long-term sustainability of a family business. A qualitative methodology is used based on the documental analysis of sustainability reporting and information collected from the company’s website and the media. This chapter present a case that can be used in management and accounting classes at both the bachelor and master levels. It is an important topic for users of financial information, entrepreneurs and other stakeholders concerned with these issues.